Post-activation Potentiation: Increasing Power Output in the Block Power Clean - Wilson, Dennis Ray (East Carolina University, 2016)
The effect of post-activation potentiation has been shown to increase both jumping height and sprinting over short distances (Wilson, et al., 2013). PURPOSE: The purpose of this study was to examine if a PAP protocol could also enhance bar-velocity (m/s) in the block power clean, a movement commonly used in strength and conditioning to enhance explosive athletic attributes such as jumping and sprinting. METHODS: ECU throwers (n=6, 67% male) participated in two session separated by three to 14 days. The first session consisted of a three-to-five repetition max of the block power clean using the Auto-regulated Progressive Resistance Exercise method, vertical jump, and a training history questionnaire. During the second session, participants performed a series of trials testing peak bar-velocity of the block power clean following a 6-second maximum voluntary isometric contraction (MVIC). Rest times were counter-balanced, varied between 15 and 120 seconds of rest between the MVIC and block power clean. Mean differences and effect sizes were calculated on the peak bar-velocities. RESULTS: Our results indicate that 15, 30, 90, and 120 seconds rest increase the peak bar-velocity. The highest effect size (ES= 1.159) and mean difference (MD= 0.123) were seen with 90 seconds of rest compared to the baseline. CONCLUSION: These initial findings suggest that the effects of post-activation Potentiation can increase peak bar-velocity of the block power clean in collegiate athletes when given appropriate rest. These finding hold important implications for training applications, however, further analysis and testing is needed.
Keywords: Post-activation Potentiation; strength and conditioning; athletics